Comparative Analysis of Gene Expression in Periodontal Ligament Stem Cells Exposed to Biodentine and Bio-C Repair: Implications for Cementogenesis—An In Vitro Study - Mahmoud M. Bakr; Mahmoud Al Ankily; Mohammed Meer; Mohamed Shamel (Oral)
Background/Objectives: Bioactive materials are gaining increased popularity as materials of choice for pulpal regeneration. A similar trend is emerging with root repair materials; however, there is a significant gap in the literature about cementogenic ability of bioceramic repair materials on the periodontal ligament cells. The aim of the present study was to investigate the effect of bioceramic materials (Biodentine and Bio-C Repair) on the cementogenesis potential of the periodontal ligament stem cells (PDLSCs). Methods: PDLSCs were isolated using the enzymatic digestion approach from sound extracted teeth. Material extracts were prepared on rubber discs and immersed in fresh growth medium for 24 h at 37 °C. Reverse transcription–quantitative polymerase chain reaction (RT-qPCR) was used to detect the mRNA expression levels of cementogenic markers cementum protein 1 (CEMP1), Cementum attachment protein (CAP), pathway markers transforming growth factor β1(TGF-β1), bone morphogenic protein 2 (BMP2), and inflammatory marker IL-6. Results: Both materials (Biodentine and Bio-C Repair) showed significantly higher gene expressions when compared to the control groups. The gene expression with Bio-C Repair significantly increased when compared with Biodentine, except for TGF-β1 expression, where both materials exhibited similar results. Conclusions: Bio-C Repair demonstrated increased gene expression of cementogenic markers compared to Biodentine under the tested conditions. Further in vivo studies are deemed necessary to translate the findings from this study into clinical practice.